MEDULLARY CARCINOMA OF THE BREAST-EPIDEMIOLOGY, THE PATTERN OF CARE, AND TREATMENT OUTCOME: EXPERIENCE FROM THE TERTIARY CANCER CARE CENTER - DUTTA, SHATARUPA; BANERJEE, SAPTARSHI; BERA, ANJAN; MANDAL, SRIKRISHNA; BANERJEE, CHANDRIMA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Medullary breast carcinoma is a very rare subtype of invasive ductal carcinoma breast which accounts for about 1–7% of all breast carcinoma. The natural history of this uncommon histological subtype is unknown because of the lack of adequate reported data in the literature and the rare variety of this tumor. In our retrospective analysis, we have tried to identify demographic clinicopathological features and treatment outcomes of this rare subtype. Methods: Between January 2012 and December 2017, total of 1271 breast carcinoma cases were identified, and clinic pathological, demographic profile, and treatment received were recorded from the medical records file. American joint committee on Cancer tumor, node, and metastasis system was used for staging. Results: Out of 1271 breast carcinomas, 19 histologically confirmed medullary carcinoma cases were identified and constitute about 1.5% of the total case. About 78% of patients were with Stage II and Stage III disease at the time of diagnosis. Eleven patients were initially treated with MRM followed by adjuvant chemotherapy and radiotherapy. Eight patients received neoadjuvant chemotherapy followed by surgery and radiotherapy. In addition to cytotoxic chemotherapy, two patients received trastuzumab also. None of the patients received hormone therapy as all the patients were hormone receptor-negative. Conclusions: Out of all invasive carcinoma, approximately 1.5% of cases were medullary carcinoma. About 90% of cases were triple-negative. Triple-negative breast cancer is usually associated with poor outcomes but medullary carcinoma despite being triple-negative, patients with medullary carcinoma have a good chance of long-term survival.